2017
DOI: 10.5897/jvmah2016.0499
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of endo-parasites in donkeys and camels in Karamoja sub-region, North-eastern Uganda

Abstract: Donkeys (Ass-Equus-assinus) and camels (Camelus dromedarius) in 3%) and donkeys (15.4%). Coccidia species included Eimeria cameli (11%) and Eimeria Leuckarti (3.85%) in camels and donkeys, respectively. Trematodes were detected in 5 camels as Fasciola gigantica. Overall, EPG count was observed for strongyles at 58.5% in camels and 42.3% in donkeys. The results of this study will provide insights into the health of donkeys and camels in Uganda and provide a way forward to their veterinary care and management fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 6 publications
(5 reference statements)
1
5
1
Order By: Relevance
“…Different studies conducted in several countries observed a range of 2-80% E. leuckarti widespread, for instance, the prevalence ranged 4.5-5.88% in Turkey (Studzińska et al, 2008), which is close to the overall prevalence of coccidia (4.31%) observed in the present study. In line with the observations of the current study, Nakayima et al (2017) found the occurrence of gastrointestinal cestodes to be less in donkeys. However, Belay et al (2016) recorded a prevalence of 3.7% of cestodes as compared to 1.53% observed in the current study.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Different studies conducted in several countries observed a range of 2-80% E. leuckarti widespread, for instance, the prevalence ranged 4.5-5.88% in Turkey (Studzińska et al, 2008), which is close to the overall prevalence of coccidia (4.31%) observed in the present study. In line with the observations of the current study, Nakayima et al (2017) found the occurrence of gastrointestinal cestodes to be less in donkeys. However, Belay et al (2016) recorded a prevalence of 3.7% of cestodes as compared to 1.53% observed in the current study.…”
Section: Discussionsupporting
confidence: 92%
“…All eggs/oocyst of GIPs were counted and identified based on their morphology. The number of eggs/oocysts per grams of feces was calculated using the following formula (Nakayima et al, 2017):…”
Section: Sample Size and Fecal Egg Countingmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be related to their worldwide distribution and being from most pathogenic nematode parasites of equine wherever there are grasslands (Johnstone, 2000). The challenge of mixed infections exacerbates the compromised health condition of the animal which could result in debilitation and death of the animal (Jesca et al, 2016). Ethiop.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the reported range of Eimeria infections from dromedary camels in Iran is 9.51%-63% (Khodakaram-Tafti et al, 2000;Yakhchali & Cheraghi, 2007;Borji et al, 2009;Yakhchali & Atari, 2010;Kheirandish, Nourollahi-Fard & Faryabi, 2012;Sazmand et al, 2012;Radfar & Gowhari, 2013). E. cameli was reported in 11% of examined camels in Uganda (Nakayima et al, 2017). Djerbouh et al (2018) reported E. dromedarii and E. cameli, in 9.6% of the samples, and in Egypt, Abbas et al (2019) reported E. cameli-like parasites in 31%, E. rajasthani in 18%, and E. dromedarii in 14% of examined animals.…”
Section: Discussionmentioning
confidence: 99%